2019
DOI: 10.4049/jimmunol.1801118
|View full text |Cite
|
Sign up to set email alerts
|

Dragotcytosis: Elucidation of the Mechanism for Cryptococcus neoformans Macrophage-to-Macrophage Transfer

Abstract: Cryptococcus neoformans is a pathogenic yeast capable of a unique and intriguing form of cell-to-cell transfer between macrophage cells. The mechanism for cell-to-cell transfer is not understood. In this study, we imaged mouse macrophages with CellTracker Green 5-chloromethylfluorescein diacetate–labeled cytosol to ascertain whether cytosol was shared between donor and acceptor macrophages. Analysis of several transfer events detected no transfer of cytosol from donor-to-acceptor mouse macrophages. However, bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 38 publications
6
41
1
1
Order By: Relevance
“…The extrusion (vomocytosis) phenomenon, already described for C. neoformans – Ac , was also observed for all the instances tested at distinct rates. However, our conditions do not distinguish whether these events are regurgitation of ingested yeasts by amoeba or a fungal‐triggered exocytosis event as recently described for the C. neoformans –macrophage interaction (Dragotakes, Fu, & Casadevall, ). The interaction of the dimorphic fungus P. brasiliensis and Ac has not been described previously; however, Ac could also work as a potential host for the filamentous environmental phase or when returning from pathogenic phase to the environment (Arantes, Theodoro, Teixeira Mde, Bosco Sde, & Bagagli, ; Boyce & Andrianopoulos, ).…”
Section: Discussionmentioning
confidence: 69%
“…The extrusion (vomocytosis) phenomenon, already described for C. neoformans – Ac , was also observed for all the instances tested at distinct rates. However, our conditions do not distinguish whether these events are regurgitation of ingested yeasts by amoeba or a fungal‐triggered exocytosis event as recently described for the C. neoformans –macrophage interaction (Dragotakes, Fu, & Casadevall, ). The interaction of the dimorphic fungus P. brasiliensis and Ac has not been described previously; however, Ac could also work as a potential host for the filamentous environmental phase or when returning from pathogenic phase to the environment (Arantes, Theodoro, Teixeira Mde, Bosco Sde, & Bagagli, ; Boyce & Andrianopoulos, ).…”
Section: Discussionmentioning
confidence: 69%
“…There was a complete lack of a host or pathogen phenotype in the presence of antibody opsonin. This contradicts many in vitro cryptococcal studies, where 18B7 antibody is said to be required for phagocytosis by macrophage and macrophage like cell lines to occur (36).…”
Section: Discussionmentioning
confidence: 75%
“…Events of lateral transfer have been observed for Scedosporium apiospermum and Lomentospora prolificans (Trzaska, 2018), although due to spore germination, the accepting macrophage is lysed shortly after the event. It is therefore uncertain whether these are bona fide vomocytosis events followed by phagocytosis, as reported for Cryptococcus (Dragotakes et al, 2019), or a different but related process.…”
Section: Who Is Able To Vomocytose?mentioning
confidence: 99%
“…Recently, Dragotakes et al showed that lateral transfer is the combination of a nonlytic exocytosis event followed by phagocytosis by a nearby macrophage (Dragotakes, Fu, & Casadevall, 2019). It is therefore uncertain whether these are bona fide vomocytosis events followed by phagocytosis, as reported for Cryptococcus (Dragotakes et al, 2019), or a different but related process. It is therefore uncertain whether these are bona fide vomocytosis events followed by phagocytosis, as reported for Cryptococcus (Dragotakes et al, 2019), or a different but related process.…”
Section: Who Is Able To Vomocytose?mentioning
confidence: 99%
See 1 more Smart Citation